Are Changes in Sleep Quality/Quantity or Baseline Sleep Parameters Related to Changes in Clinical Outcomes in Patients With Nonspecific Chronic Low Back Pain?: A Systematic Review. Issue 4 (22nd April 2022) - Chang, Jeremy R.; Wang, Xiaoyue; Lin, Guohui; Samartzis, Dino; Pinto, Sabina M.; Wong, Arnold Y.L.
Abstract : Objectives: Sleep disturbance is prevalent among patients with chronic low back pain (CLBP). This systematic review aimed to summarize the evidence regarding the: (1) temporal relations between changes in sleep quality/quantity and the corresponding changes in pain and/or disability; and (2) role of baseline sleep quality/quantity in predicting future pain and/or disability in patients with CLBP. Methods: Four databases were searched from their inception to February 2021. Two reviewers independently screened the abstract and full text, extracted data, assessed the methodological quality of the included studies, and evaluated the quality of evidence of the findings using the Grading of Recommendations Assessment Development and Evaluation (GRADE). Results: Of 1995 identified references, 6 articles involving 1641 participants with CLBP were included. Moderate-quality evidence substantiated that improvements in self-reported sleep quality and total sleep time were significantly correlated with the corresponding LBP reduction. Low-quality evidence showed that self-reported improvements in sleep quality were related to the corresponding improvements in CLBP-related disability. There was conflicting evidence regarding the relation between baseline sleep quality/quantity and future pain/disability in patients with CLBP. Discussion: This is the first systematic review to accentuate that improved self-reported sleep quality/quantity may be associated with improved pain/disability, although it remains unclear whether baseline sleep quality/quantity is a prognostic factor for CLBP. These findings highlight the importance of understanding the mechanisms underlying the relation between sleep and CLBP, which may inform the necessity of assessing or treating sleep disturbance in people with CLBP.